Correlation Between Angle Parameters and Central Corneal Thickness in Fuchs Endothelial Corneal Dystrophy - Watanabe, Shinya; Oie, Yoshinori; Miki, Atsuya; Soma, Takeshi; Koh, Shizuka; Kawasaki, Satoshi; Tsujikawa, Motokazu; Jhanji, Vishal; Nishida, Kohji (Cornea, 2020)
To evaluate the correlation between anterior chamber parameters and central corneal thickness (CCT) or peripheral corneal thickness (PCT) in patients with Fuchs endothelial corneal dystrophy (FECD) using anterior segment optical coherence tomography. This case-control study included 20 eyes from 20 patients with FECD and 31 eyes from 31 patients with healthy corneas. CCT was measured as an indicator of FECD severity. Anterior chamber angle parameters, including trabecular-iris angle (TIA500) and angle opening distance (AOD500), were measured as an indicator of peripheral anterior chamber morphology. We also analyzed PCT and lens vault (LV). The relationships between CCT or PCT and anterior chamber parameters were also analyzed in patients with FECD. Patients with FECD had a larger CCT (593.9 ± 54.6 μm vs. 533.0 ± 25.4 μm, P < 0.001), smaller TIA500 (21.8 ± 9.9 vs. 32.5 ± 11.2 degrees, P = 0.002), smaller AOD500 (0.21 ± 0.11 vs. 0.34 ± 0.18 mm, P = 0.002), and greater LV (0.60 ± 0.27 vs. 0.40 ± 0.29 mm, P = 0.02) than control subjects. In patients with FECD, CCT was negatively correlated with the angle parameters TIA500 (R = 0.29, P = 0.009) and AOD500 (R = 0.19, P = 0.03). There were no significant correlations between PCT and TIA500 (R = 0.008, P = 0.29) or AOD500 (R = 0.007, P = 0.29). There were also no significant correlations between CCT and LV (R = 0.02, P = 0.55). Larger CCT was significantly associated with narrower anterior chamber angle width, but not with LV. We showed that the severity of FECD is associated with angle chamber morphology.